Pracownicze oceny okresowe — wybrane elementy - Górnicz-Mulcahy, Agnieszka (Wydawnictwo Uniwersytetu Wrocławskiego, 2020)
Periodic employee evaluations are now a permanent element of the employment relationship. The evaluation mechanism existing in the public service also provides for negative effects related to the process of periodic evaluations. The aim of the article is to point out that the main purpose of periodic evaluations is, however, their positive dimension, aimed at the employee’s professional development process, improving his qualifications and developing competences. On the basis of worker pragmatics, this task is difficult because the employer’s behaviour is not free but should focus on the assessment of certain normative criteria using an objective measure (Article 94 point 9 of the Labour Code).
Keywords: employment relationship; periodic employee evaluation; fair and objective criteria